Dissociative disorder in Mayer Rokitansky Küster Hauser syndrome with pulmonary agenesis: a case report - Sulochana Joshi; Anup Raj Bhandari; Prashant Shrestha; Rabi Shakya (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Abstract Background The Mayer Rokitansky Küster Hauser (MRKH) syndrome is a rare congenital disorder characterized by the absence of uterus and vagina in a patient who is phenotypically a female, with 46 XX karyotypes. It affects 1 in 4000 to 5000 female new-borns. Pulmonary agenesis is a rare association in this MRKH syndrome. Females with MRKH face various mental health issues and psychological disturbances, including dissociative disorder which is a stress-related psychiatric disorder. Dissociative disorder in MRKH syndrome is under-recognized and under-treated. Case presentation A 23-year-old unmarried woman presented to the emergency forabnormal behaviour attack. Recurrent episodes of dissociative convulsions were present most of the time with MRKH syndrome as the pertinent stressor. Both antidepressants and psychotherapy helped to decrease the frequency of dissociative convulsions and come interms with the syndrome. Conclusion This case describes dissociative disorder as the presentation and comorbid condition of MRKH syndrome and the impact of MRKH syndrome on the patient. We attempt to explain the occurrence of dissociative disorder in MRKH syndrome and the results of under-recognition and under-treatment of the same. We aim to highlight the presence of commonly treatable conditions associated with a rare syndrome and its effect when untreated and unrecognized.